ZTTK syndrome: Clinical and molecular findings of 15 cases and a review of the literature. Issue 12 (31st July 2021) - Kushary, Sulagna Tina; Revah‐Politi, Anya; Barua, Subit; Ganapathi, Mythily; Accogli, Andrea; Aggarwal, Vimla; Brunetti‐Pierri, Nicola; Cappuccio, Gerarda; Capra, Valeria; Fagerberg, Christina R.; Gazdagh, Gabriella; Guzman, Edwin; et al.
Abstract: Zhu‐Tokita‐Takenouchi‐Kim (ZTTK) syndrome is caused by de novo loss‐of‐function variants in the SON gene (MIM #617140). This multisystemic disorder is characterized by intellectual disability, seizures, abnormal brain imaging, variable dysmorphic features, and various congenital anomalies. The wide application and increasing accessibility of whole exome sequencing (WES) has helped to identify new cases of ZTTK syndrome over the last few years. To date, there have been approximately 45 cases reported in the literature. Here, we describe 15 additional individuals with variants in the SON gene, including those with missense variants bringing the total number of known cases to 60. We have reviewed the clinical and molecular data of these new cases and all previously reported cases to further delineate the most common as well as emerging clinical findings related to this syndrome. Furthermore, we aim to delineate any genotype–phenotype correlations specifically for a recurring pathogenic four base pair deletion (c.5753_5756del) along with discussing the impact of missense variants seen in the SON gene.